Gene Effect of Morphophysiological Traits in Popcorn (Zea mays L. var. everta) Grown Under Contrasting Water Regimes - Danielle Leal Lamêgo; Antônio Teixeira do Amaral Junior; Samuel Henrique Kamphorst; Valter Jário de Lima; Samuel Pereira da Silva; Jardel da Silva Figueiredo; Ueliton Alves de Oliveira; Flávia Nicácio Viana; Talles de Oliveira Santos; Gabriella Rodrigues Gonçalves; Guilherme Augusto Rodrigues de Souza; Eliemar Campostrini; et al. (Agriculture)
To propose breeding strategies for drought conditions, we investigated gene expression associated with morphophysiological traits in four S7 popcorn (Zea mays var. everta) inbred lines using a partial diallel cross design with two testers. We evaluated morphological traits (plant height; the dry mass of stems, leaves, and reproductive organs; and root weight density (RWD) across five soil sections), water status indicators (leaf water content, cumulative evapotranspiration, agronomic water use efficiency, and carbon isotope signatures), anatomical traits (stomatal number and index), and leaf pigments. Significant variations were observed between lines and hybrids for plant height, shoot biomass traits, water status indicators, and RWD across all soil sections, particularly under water deficit conditions. Overall, the inbred lines were more adversely affected by drought than the hybrids. Dominance gene effects played a significant role in increasing anthocyanin content, cumulative evapotranspiration, stable carbon isotope signatures, and RWD in most soil sections. The superior water utilization observed in hybrids compared to inbred lines suggests that exploiting heterosis is likely the most effective strategy for developing drought-resilient popcorn plants.